Defining and using a system of measurement for quality performance of science teachers training in Indonesia - Guyub, Haryanto (Animo Repository, 2005)
The qualified science teacher is considered as the best determinant factor for quality improvement in pursuing science education in Indonesia. In terms of pre service training, there are some things 'missing' in their skills, knowledge, and attitudes gained from the teacher preparation. The function of in-service training is bridging the gap between existing and required knowledge, skills and attitudes of teachers, so that they perform at the minimum competence when starting the teaching process in school. The study was designed to define and use a measurement system for quality performance of the in-service training for science teachers. The quality performance is caused by the operating performance of the structural factors of the management of the science teachers training. This idea leads the researcher to consider that this study is a Confirmatory Research. The respondents of this research are science teachers and the schoolmasters, and the faculty members of the Center. The research process used a modified benchmarking approach. Whereas, the variables as were culled from literature, were established through a Focus Group Discussion among the authoritative individuals on the subject in the country. The standards set of variables and measures became the benchmark against which operating performance of the Center was measured. The collected data was processed and analyzed by utilizing Structural Equation Modeling (SEM) and the application of LISREL software as a technique in multivariate data analysis and known as Confirmatory Factor Analysis (CFA). An effective performance measurement system that may be adapted by the Center as a continuing yardstick for Total Quality Management was developed by using the most significant variables with highest direct effect on the respective structural factors of the science teachers training. Although it appears that the science teachers' development falls within a human resources development perspective in so far as their respective schools are concerned, a corresponding strategic approach of improvement is likewise imperative within the management of the science teachers training.